Country Partnership Framework for the Democratic Republic of Timor-Leste for the Period FY2020 - FY2024 - World Bank Group (World Bank, Washington, DC, 2019)
The Country Partnership Framework (CPF) outlines the principles underlying the World Bank Group’s engagement with Timor-Leste from FY2020 to FY2024. The CPF responds to Timor-Leste’s strategic directions and its timeframe coincides with the expected tenure of the current parliament and government - the VIII Constitutional Government – and its Five-Year Implementation Plan (2018-2023) that supports Timor-Leste’s Strategic Development Plan (SDP) 2011-2030. The CPF covers three focus areas: (i) strengthen the foundation for private sector-led growth and economic stability; (ii) invest in human capital, service delivery and promote gender equity; (iii) raise productivity through investments in connective infrastructure; and a cross-cutting theme on governance, focusing on strengthening institutional and implementation capacity in government.